Architecture of the Sporulation-Specific Cdc14 Promoter from the Oomycete Phytophthora infestans - Ah-Fong, Audrey M. V. (American Society for Microbiology (ASM), 2007)
The Cdc14 gene of Phytophthora infestans is transcribed specifically during sporulation, with no mRNA detectable in vegetative hyphae, and is required for sporangium development. To unravel the mechanisms regulating its transcription, mutated Cdc14 promoters plus chimeras of selected Cdc14 sequences and a minimal promoter were tested in stable transformants. This revealed that a tandem repeat of three copies of the motif CTYAAC, located between 67 and 90 nucleotides (nt) upstream of the major transcription start site, is sufficient to determine sporulation-specific expression. All three repeats need to be present for activity, suggesting that they bind a transcription factor through a cooperative mechanism. Electrophoretic mobility shift assays indicated that the CTYAAC repeats are specifically bound by a protein in nuclear extracts. Evidence was also obtained for a second region within the promoter that activates Cdc14 transcription during sporulation which does not involve those repeats. The CTYAAC motif also affects the specificity of transcription initiation. Wild-type Cdc14 is transcribed from a major start site and minor site(s) located about 100 nt upstream of the major site. However, stepwise mutations through the CTYAAC triad caused a graded shift to the upstream sites, as did mutating bases surrounding the major start site; transcripts initiated from the upstream site remained sporulation specific. Replacing the Cdc14 initiation region with the Inr-like region of the constitutive Piexo1 gene had no apparent effect on the pattern of transcription. Therefore, this study reports the first motif determining sporulation-induced transcription in oomycetes and helps define oomycete core promoters.